2021
DOI: 10.1016/j.heliyon.2021.e07652
|View full text |Cite
|
Sign up to set email alerts
|

Water hyacinth plant extract mediated green synthesis of Cr2O3/ZnO composite photocatalyst for the degradation of organic dye

Abstract: The Cr 2 O 3 /ZnO composite catalysts with varying the amount of chromium precursors abbreviated as 0.02CrZn, 0.04CrZn, 0.06CrZn, 0.08CrZn, 0.1CrZn, and fixed the amount of Zn precursor (0.1 M) were prepared by using water hyacinth (Eichhornia crassipes) extract as a template/capping agent. The prepared catalysts were characterized and the catalytic performances of the catalysts were also checked for the degradation of methylene blue (MB) dye. The photocatalytic MB dye degradation by 0.08CrZn catalyst was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 57 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Currently, reports on a ZnO-based photocatalyst are available [15][16][17][18]. For example, the prepared ZnO from Acremonium potronii for dye degradation was reported by Ameen et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, reports on a ZnO-based photocatalyst are available [15][16][17][18]. For example, the prepared ZnO from Acremonium potronii for dye degradation was reported by Ameen et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their excellent stability, hardness, high resistivity, high melting temperature, and wide bandgap of 3.4 eV, chromium oxide nanoparticles (Cr 2 O 3 ) have grained particular among metal oxide NPs (Iqbal et al, 2020;Isacfranklin et al, 2020). Cr 2 O 3 NPs could be used in materials for catalysis (Mori et al, 2017), photocatalysis (Zelekew et al, 2021), super capacitors (Shafi et al, 2021), lithium ion batteries (Cao and Zuo, 2017), sensing (Gao et al, 2019), and other biological activities due to their unique properties (Talat et al, 2021). Biocompatibility of Cr 2 O 3 nanoparticles is an essential parameter for their use in many biological systems (Khan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Besides these, the amorphous phase of silica is highlighted at 25 2θ [ 34 ]. After introducing and increasing the concentration of zinc oxide, it is observed that major changes occur only at the concentration of 0.1g ZnO in the material [ 35 ].…”
Section: Resultsmentioning
confidence: 99%